Kontekstualisasi Gharar di Era Digital: Tinjauan Fikih Muamalah terhadap Validitas Objek Akad (Ma'qud 'Alaih) pada E-Commerce - Aat Supriatna; Abdul Gofur (Penerbit Lestari Sakha Pustaka, 2026)
The rapid growth of the e-commerce ecosystem in Indonesia has fundamentally changed muamalah interactions from face-to-face patterns (mujwajahah) to virtual transactions without physical boundaries. However, this transformation leaves crucial Islamic legal issues, particularly regarding the physical absence of the contract object (ma'qud 'alaih) during the transaction. In classical fiqh discourse, the absence of the object (ghayb al-majlis) is often associated with gharar (uncertainty), which can invalidate the contract due to the high potential for fraud and information asymmetry. This study aims to reconstruct the concept of gharar in the context of the digital economy and formulate validity parameters for contract objects on e-commerce platforms based on contemporary Fiqh Muamalah perspectives. The method employed is normative legal research (juridical-normative) with a qualitative approach. The author collects data through library research on cross-madhhab classical books (turats), DSN-MUI fatwas, and marketplace regulations, which are then analyzed using content analysis techniques and the qiyas (analogy) method. The results indicate an epistemological shift in interpreting contract validity requirements. First, the concept of